The Albert Bender donations of Far Eastern Art to the National Museum of Ireland in the context of his cultural interests in Ireland and California - Whitty, Audrey (Trinity College (Dublin, Ireland). Department of History of Art and Architecture, 2010)
The National Museum of Ireland (formerly the Dublin Science and Art Museum) was founded in 1877. During the late nineteenth/early twentieth century policy dictated that the acquisition of applied/industrial arts be nationally as well as internationally based. As a result many objects of Asian provenance came under museum control. This policy changed on Irish Independance, but one notable donor during the early years of the Irish Free State was the Irish-born, San Francisco millionaire, Albert Maurice Bender (1866-1941) who donated 260 objects of Asian art from 1931 to 1936. This collection includes twenty -one rare eighteenth century’ Tibetan-Buddhist Thangka paintings and over eighty Japanese woodblock prints from the eighteenth and nineteenth centuries. Bender’s Jewish faith and Irish patriotism are examined in the context of his collecting activities, his generous benefaction of contemporary avant-garde art on the west coast of the United States and extensive bibliophilic activities. Bender’s correspondence with the director of the National Museum, Dr. Adolf Mahr will also be discussed, as will his relationships with some of Ireland’s most prominent intellectuals.
Keywords: History of Art and Architecture, Ph.D.; Ph.D. Trinity College Dublin